Can agroecological transition of intensive cereal system of Indo-Gangetic plains deliver sustainable and nutritious food? - Gora, M.K.; Kumar, Satish; Jat, Hanuman Sahay; Kakraliya, S.; Choudhary, Madhu; Dhaka, A.K.; Jat, Raj Kumar; Kakraliya, Manish; Sharma, Parbodh Chander; Jat, Mangi Lal (Research Square Platform LLC, 2022)
Indo-Gangetic plains (IGP) of South Asia have supported bulk of human and bovine population in the region since ages, and a spectacular progress has been made here on food production. However, this cereal-system-dominated region still suffers with challenges of malnourishment, declining total factor productivity and natural resource degradation with potential threats of climate change. Addressing these challenges would require a transition towards agroecological cropping systems. A study was, therefore, conducted on crop diversification and sustainable intensification options using agro-ecological approaches such as Conservation Agriculture (CA) to ensure food and nutritional security while sustaining the natural resources. On 2 years mean basis, CA-based cropping system management scenarios (mean of Sc2-Sc7) using diversified rotations; increased the system yield by 15.4%, net return by 28.7%, protein yield by 29.7%while using 53.0% less irrigation water compared to conventional tillage (CT)-based rice-wheat system (Sc1). Maize-mustard-mungbean on permanent beds (Sc4) recorded the highest productivity (+40.7%), profitability (+60.1%), and saved 81.8% of irrigation water compared to Sc1 (11.8 Mg ha-1; 2190 USD ha-1; 2514 mm ha-1). It was closely followed by Sc5 (32.3, 57.4, 413.8, 75.5%) i.e. maize-wheat-mungbean on permanent beds. In terms of nutritional value, Sc5 was more balanced than other scenarios, and produced 43.8, 27.5 and 259.8% higher protein, carbohydrate and fat yields, respectively, compared to Sc1 (0.93, 8.55 and 0.14 Mg ha-1). Scenario 5 was able to meet the nutrient demand of 19, 23 and 32 more persons ha-1 year-1 with respect to protein, carbohydrate and fat demand, respectively, compared to Sc1 (44, 86 and 13 persons ha-1 year-1).However, the highest protein and fat yield and their adult equivalents was associated with Sc6 (soybean based) and Sc4 (maize based), respectively. Soybean based system (Sc6) was economically more efficient with respect to nutrients than other systems. Mungbean integration improved the system productivity by 17.2 % and profitability by 32.1%, while improving the irrigation water productivity by three times compared to CT-based systems. In western IGP, CA-based maize-wheat-mungbean system was the most productive, profitable and nutritionally rich and efficient system compared to other systems. Therefore, CA- based crop diversification is an option to ensure quality and nutritious food for the dwelling communities in the region.